Bioleaching of different copper sulphide minerals and their physicochemical properties dependence. (2nd January 2016) - Fu, K.; Ning, Y.; Chen, S.; Wang, Z.
Abstract : This paper investigated the bioleaching of different copper sulphide minerals. The bioleaching experiments show that the order of the copper bioleaching rates of four copper sulphide minerals, regardess of whether the optimum conditions or the initial ferrous iron concentration of 0 g L − 1, was identical: djurleite> bornite> covellite> chalcopyrite. Properties of mineral, such as rest potential, lattice energy, conductivity type and solubility product constant, are the intrinsic factors influencing the bioleaching of minerals. Among these parameters, rest potential and lattice energy can explain the difference of the bioleaching of four copper sulphide minerals. Conductivity type can interpret the low copper leaching efficiency of chalcopyrite and covellite. However, it cannot explicate the high copper leach rate of djurleite and bornite. The decrease of the lag phase of Acidithiobacillus ferrooxidans with an increase of solubility product constant of minerals is observed in the bioleaching system of four copper sulphide minerals. However, solubility product constant is not the crucial parameters dominating the bioleaching efficiency of copper sulfide minerals.